Rola rolnictwa w regionach o niekorzystnych warunkach gospodarowania (przykład Hiszpanii i Portugalii) - Piecuch, Jakub (The Role of Spanish and Portuguese Less-Favoured Agriculture Regions, 2006)
The importance of less-favoured areas was recently recognized, because the great part of Europe is covered by mountain ranges and islands. This approach can be especially observed in Spain and Portugal. These regions have permanent natural handicaps, due to peripherality and topographic and climatic restrictions. In many of these areas of the Iberian peninsula, small-scale and low-tech agriculture still dominate. In most cases these regions are considered to be areas which traditional economy is not adapted to market conditions. Agriculture is a crucial sector for Portuguese islands economies and modernization of primary sector seems to be for them the most important priority. Also infrastructure provision in these areas is less developed and of poorer quality than in other parts of Europe. These factors cause that European cohesion policy has an important role to play in dynamizing economic growth and sustaining the welfare of inhabitants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 226-233